ANÁLISE DE FATORES PROGNÓSTICOS E EXPRESSÃO IMUNO-HISTOQUÍMICA DA PROTEÍNA KI67 DE PACIENTES COM CÂNCER DE PÊNIS QUE FORAM SUBMETIDOS A LINFADENECTOMIA REGIONAL NO ESTADO DO MARANHÃO. - NASCIMENTO, Athienne Driele Maniva Teixeira do (2018)
Penile cancer is a public health issue in the state of Maranhão and has the highest incidence ever documented in literature. The presence of lymph node metastasis is the main prognostic factor associated with survival. Health systems’ major challenge concerning penile cancer is the identification of factors that may impact the prognosis of patients and the discovery of biomarkers capable of contributing to the treatment of these patients, especially regarding the indication for lymphadenectomy since there are no markers to identify the presence of lymph node metastasis. The aim of this study was to analyze prognostic factors and the immunohistochemical expression of Ki67 protein in penile cancer patients who underwent regional lymphadenectomy in the state of Maranhão between January 2009 and September 2017. We reviewed medical records, interviewed patients who were diagnosed with the disease and established a periodic review of the electronic medical record to follow-up of the patient’s status. Fifty-five cases were analyzed with an average age of 55.4 years being the average time between the onset of symptoms and the onset of treatment of 24.4 months. The presence of angiolymphatic invasion (p=0.029) and the absence of koilocytosis (p=0.001) were predictive factors for lymph node metastasis. Patients who underwent prophylactic lymphadenectomy presented a 5.5 months longer disease-free survival when compared to patients who underwent the procedure belatedly.